Rotavirus alphagastroenteritidis: Circulating Strains After the Introduction of the Rotavirus Vaccine (Rotarix®) in Luanda Province of Angola - Dikudila G. Vita; Cristina Santiso-Bellón; Manuel Lemos; Zoraima Neto; Elsa Fortes-Gabriel; Miguel Brito; Cruz S. Sebastião; Jesus Rodriguez-Diaz; Celso Cunha; Claudia Istrate (Viruses)
Rotavirus alphagastroenteritidis (R. alphagastroenteritidis) remains the leading cause of pediatric diarrhea. Although Angola introduced Rotarix®, the human monovalent R. alphagastroenteritidis vaccine since 2014 as part of its routine childhood immunization program, no follow-up study has been conducted. The aim of this study was to evaluate the distribution of R. alphagastroenteritidis genotypes among children under five years of age, hospitalized with acute gastroenteritis (AGE), after the introduction of the rotavirus vaccine. To achieve this goal, stool samples collected between 2021 and 2022 from children under 5 years of age diagnosed with AGE at six hospitals in Luanda Province were analyzed. The R. alphagastroenteritidis-antigen immunochromatographic test (SD Bioline™, Abbott, Chicago, IL, USA) was performed, and 121 positive samples were genotyped. Ten samples were randomly selected for further Sanger sequencing. The results showed that the G9P[6] was the most prevalent genotype (17.3%), followed by G9P[8] (16.5%), G2P[4] (14.9%), G3P[6] (13.2%), G8P[6] (11.5%), and less frequently G12P[8] (9.1%), G1P[6] (4.1%), and G1P[8] (2.5%). The genotype combinations G3P[6], G8P[6], and G12P[8] were detected for the first time in Luanda Province. In conclusion, the emergence of new genotype combinations supports the need for continuous surveillance to identify the trend in R. alphagastroenteritidis infection and the emergence of new strains circulating in Luanda Province in the post-vaccination period.